One-loop impact factors for heavy quarkonium production: S-wave case - Maxim A. Nefedov (Journal of High Energy Physics)
Abstract With the aim to extend the study of inclusive heavy quarkonium production at forward rapidities with the resummation of high partonic center-of-momentum-energy logarithms beyond Leading Logarithmic Approximation (LLA), the explicit analytic results for one-loop corrections to the following impact factors had been obtained: γR → Q Q ¯ S 1 0 8 $$ Q\overline{Q}\ \left[{^1S}_0^{\left[8\right]}\right] $$ , gR → Q Q ¯ S 1 0 1 $$ Q\overline{Q}\ \left[{^1S}_0^{\left[1\right]}\right] $$ , gR → Q Q ¯ S 1 0 8 $$ Q\overline{Q}\ \left[{^1S}_0^{\left[8\right]}\right] $$ and gR → Q Q ¯ S 3 1 8 $$ Q\overline{Q}\ \left[{^3S}_1^{\left[8\right]}\right] $$ , with R being the Reggeized gluon and Q is the heavy quark. The computation is done in the framework of Lipatov’s gauge-invariant EFT for Multi-Regge processes in QCD with the tilted-Wilson-line regularisation for rapidity divergences. As expected, only single-logarithmic rapidity divergence proportional to the one-loop Regge trajectory of a gluon remains in the final result for impact-factors. Numerical comparison with Regge limits (s/(–t) ≫ 1) of one-loop QCD amplitudes, described in the paper, provides a strong cross-check of obtained results. The relations of obtained results with other regularisation schemes for rapidity divergences used in low-x physics, such as BFKL scheme, High-Energy Factorisation (HEF) scheme and shockwave scheme, are given.